2018
DOI: 10.1101/419523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phasor histone FLIM-FRET microscopy quantifies spatiotemporal rearrangement of chromatin architecture during the DNA damage response

Abstract: To investigate how chromatin architecture is spatiotemporally organised at a double strand break (DSB) repair locus, we established a biophysical method to quantify chromatin compaction at the nucleosome level during the DNA damage response (DDR). The method is based on phasor image correlation spectroscopy (ICS) of histone FLIM-FRET microscopy data acquired in live cells co-expressing H2B-eGFP and H2B-mCherry. This multiplexed approach generates spatiotemporal maps of nuclear-wide chromatin compaction that wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…FLIM has been used to study the chromatin compaction state during cell cycle progression in fixed samples where heterogeneous DNA distribution was seen (Murata et al 2000;Murata et al 2001;Görlitz et al 2017). FLIM on live interphase nuclei has shown chromatin decompaction upon chemical or radiation stimulus (Abdollahi et al 2018;Lou et al 2019;Pelicci et al 2019;Sherrard et al 2018). Live cell imaging studies have examined naive embryonic stem cells (ESCs) undergoing differentiation and showed that the presence of NANOG is essential for chromatin decompaction during pluripotency together with Rex1 downregulation (Hockings et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…FLIM has been used to study the chromatin compaction state during cell cycle progression in fixed samples where heterogeneous DNA distribution was seen (Murata et al 2000;Murata et al 2001;Görlitz et al 2017). FLIM on live interphase nuclei has shown chromatin decompaction upon chemical or radiation stimulus (Abdollahi et al 2018;Lou et al 2019;Pelicci et al 2019;Sherrard et al 2018). Live cell imaging studies have examined naive embryonic stem cells (ESCs) undergoing differentiation and showed that the presence of NANOG is essential for chromatin decompaction during pluripotency together with Rex1 downregulation (Hockings et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It will be of interest to extend this robust SIM-ICCS analysis to data acquired with faster SIM setups (38,39) and study the organization of chromatin, dynamically, in living cells. Information on the organization of chromatin functional motifs at a scale of $100 nm, extracted by SIM-ICCS, would be complementary to other live-cell methods, such as Förster resonance energy transfer, that provide spatial information on a scale below $10 nm (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, FRET is a phenomenon sensitive to fluorophore proximity that occurs efficiently only when 6 the donor and acceptor fluorescent fusion proteins are closely positioned (<10nm) in the 3D nuclear space following chromatin compaction. By measuring histone-histone proximity, this FRET assay can respond to changes in nucleosome spacing, and therefore provides a read-out of nanoscale chromatin compaction (38)(39)(40)(41). FLIM-FRET also provides accurate quantification due to the independence of the fluorescence lifetime from the relative concentrations of the interacting proteins, and is independent of their diffusion rates (42).…”
Section: Nanoscale Chromatin Compaction Is Decreased In Set-2 Mutant mentioning
confidence: 99%